Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Keterlibatan Karyawan - Wawan Saputra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The importance of leadership style and organizational culture in influencing employee engagement levels has become a primary focus in management research. Drawing on leadership and organizational culture theories, this study aims to explore the impact of these variables on employee engagement within the organizational context. The research method used is a survey through questionnaires distributed to employees from various organizational backgrounds. The data analysis technique employed is multiple regression analysis. The study's findings present the relationship between leadership style, organizational culture, and employee engagement levels by identifying key influencing factors. The findings provide a deeper understanding of how leadership style and organizational culture can influence employee engagement, as well as their practical implications in human resource management. In conclusion, this study makes a significant contribution to enriching management literature by highlighting the importance of these factors in achieving better organizational performance and higher employee engagement